Physicochemical characteristics of glucosamine from blue swimming crab (Portunus pelagicus) shell prepared by acid hydrolysis - Jittrakan Kraisangsri (2018)
© 2018, Walailak University. All rights reserved. The aim of this research was to characterize glucosamine hydrochloride (GluHCl) from the shell of blue swimming crab (Portunus pelagicus). The crab shell was finely milled and processed to chitin prior to HCl hydrolysis using 30 % HCl for 30 min at 100 ºC for glucosamine production. The resultant glucosamine was recovered by crystallization using 95 % ethanol and was dried in a hot air oven. The color of the glucosamine crystals, expressed as L*, a*, and b*, was 83.01, 5.03, and-3.38, respectively. Crab shell glucosamine had high purity, which could be strongly stained by ninhydrin and presented at the same Rf of standard D-glucosamine using thin layer chromatography. Furthermore, prepared glucosamine exhibited similar Fourier transform infrared (FTIR) spectrum as standard D-glucosamine. Glucosamine from blue swimming crab shell had high purity as determined by HPLC and contained 808.15 mg D-glucosamine/g sample. The maximal transition temperature (Tmax) and the total enthalpy (ΔH) of prepared glucosamine were 194 ºC and 754.42 J/g, respectively. As a consequence, with the presented method, the resultant glucosamine was characterized to be D-glucosamine. Therefore, blue swimming crab shell, a byproduct from crab meat processing, has high potential as a raw material to produce glucosamine for food and nutraceutical applications.